Congenital cataracts - a literature review - Monika Nowak; Julia Górczyńska; Maciej Dyda; Katarzyna Mazur-Melewska; Kinga Zimna; Hanna Zając-Pytrus (Termedia Publishing House, 2023)
Congenital cataracts are clouding of the crystalline lens inside the eye, which is present at birth and leads to a decrease in vision. It is one of the three leading causes of blindness in children, responsible for up to 27.6% of cases. The etiology of congenital cataracts varies. The main causes include heredity, chromosomal aberrations, metabolic diseases, and intrauterine infections. Early diagnosis and treatment of congenital cataracts are essential in the prevention of irreversible loss of vision. The red reflex test is an excellent tool in the screening of congenital cataracts and should be performed on each newborn. Congenital cataract therapy differs from adult cataract therapy, being based primarily on early surgical intervention. Long-term post-operative rehabilitation is also an important part of care.